The financial stability implications of digital assets - Pablo D. Azar; Garth Baughman; Francesca Carapella; Jacob Gerszten; Arazi Lubis; Juan Pablo Perez-Sangimino; David E. Rappoport; Chiara Scotti; Nathan Swem; Alexandros Vardoulakis; Aurite Werman (Federal Reserve Bank of New York, 2022)
The value of assets in the digital ecosystem has grown rapidly amid periods of high volatility. Does the digital financial system create new potential challenges to financial stability? This paper explores this question using the Federal Reserve's framework for analyzing vulnerabilities in the traditional financial system. The digital asset ecosystem has recently proven itself to be highly fragile. However, adverse digital asset market shocks have had limited spillovers to the traditional financial system. Currently, the digital asset ecosystem does not provide significant financial services outside the ecosystem, and it exhibits limited interconnections with the traditional financial system. The paper describes emerging vulnerabilities that could present risks to financial stability in the future if the digital asset ecosystem becomes more systemic, including run risks among large stablecoins, valuation pressures in crypto-assets, fragilities of DeFi platforms, growing interconnectedness, and a general lack of regulation.
Keywords: G20; G21; G28; 330; digital assets; stablecoins; DeFi; financial stability; financial vulnerabilities; systemic risk